Aspiration of breast abscess under ultrasound guidance: Outcome obtained and factors affecting success - Faisal, Elagili; Norlia, Abdullah; Liew, Fong; Tan, Pei (Elsevier, 2007)
OBJECTIVE: To assess ultrasonographically (US) guided needle aspiration of breast abscesses as an alternative to surgical incision and drainage. METHODS: In our prospective study, 30 patients with 31 breast abscesses (one patient had bilateral breast abscess) underwent percutaneous breast abscess drainage under US guidance with local anaesthesia and oral antibiotics between 1 January 2004 and 31 March 2005. These patients consisted of 16 (53.3%) nonlactating and 14 (46.7%) lactating women, with ages ranging from 18 to 68 years (median, 28 years). The racial distribution comprised 26 (86.7%) Malays, three (10%) Chinese and one (3.3%) Indian. All patients had the chief complaint of breast swelling and 25 (83.3%) had breast pain. Clinically, 28 (93.3%) were found to have a palpable mass. Nine (30%) lesions were in the upper outer quadrant of the left breast. US diameters ranged from 1 to 15 cm (median, 4 cm). The pus volumes varied from 1 to 200 mL (median, 14 mL). RESULTS: Fifteen (50%) patients required only a single aspiration, 10 required multiple aspirations and five required incision and drainage. Those patients in whom needle aspiration failed had multiloculated lesions irrespective of abscess volume and size. CONCLUSION: Needle aspiration with ultrasound guidance is an effective treatment for breast abscess irrespective of abscess volume and size. [Asian J Surg 2007;30(1):40–4]